Continuing Education on Suicide Assessment and Crisis Intervention for Social Workers and Other Mental Health Professionals: A Follow-Up Study. Issue 4 (7th August 2016) - Mirick, Rebecca G.; Bridger, Joanna; McCauley, James; Berkowitz, Larry
ABSTRACT: Historically, graduate training programs have not taught suicide assessment and intervention skills in depth; therefore, the development of effective continuing education offerings is relevant and necessary for practicing social workers. Although the ability to increase knowledge and confidence is critical, a focus on competency-based education demands that training participants also incorporate the new skills into practice. This study evaluates a 6 hour continuing education program on suicide assessment and intervention. A one-group, pretest/posttest/3-month follow-up design assessed changes in knowledge and confidence as well as participants' self-reported integration of knowledge and skills into their practice. Implications for continuing education programs on suicide assessment and intervention are discussed.